Correlation of renal cortical blood perfusion and BP response after renal artery stenting - Wang, Siyu; Zhang, Sijie; Li, Yan; Ma, Na; Li, Mengpu; Ai, Hu; Zhu, Hui; Ren, Junhong; Li, Yongjun; Li, Peng (Frontiers in Cardiovascular Medicine, 2022)
A total of 164 patients with unilateral severe RAS after successful percutaneous transluminal renal artery stenting (PTRAS) in Beijing Hospital From Jul. 2017 to Dec. 2020 were included. According to the results of APBM evaluated at 12 months, all patients were divided into BP response group (n=98) and BP nonresponse group (n=66). Among 164 patients with severe RAS, there were 100 males (61.0%), aged 37-75 years old, with an average of 56.8±18.4 years, and an average artery stenosis of 84.0%±12.5%. The BP nonresponse patients had a longer duration of hypertension, more current smoking subjects and diabetic patients, lower eGFR, increased number of hypertensive agents and rate of insulin compared with the BP response group (P<0.05). After PTRAS, patients in the BP response group were associated with significantly lower BP (dSBP, dDBP, nSBP, nDBP, 24h average SBP and 24h adverage DBP) and improved CBP, characterized by increased levels of maximum intensity (IMAX), area under ascending curve (AUC1) and area under the descending curve (AUC2), shortened rising time (RT) and mean transit time (mTT) and prolonged time to peak intensity (TTP) (P<0.05). However, the BP nonresponse group was only associated with significantly reduced RT (P<0.05) compared with baseline data. During an average follow-up of 11.5±1.7 months, the BP response group was associated with significantly lower levels of SBP, DBP, 24h average SBP and 24h average DBP compared with the nonresponse group (P < 0.05). Pearson correlation analysis showed that the the pre-operative CBP parameters, including IMAX (r=0.317), RT (r=0.249), AUC1 (r=0.614), AUC2 (r=0.558) and postoperative CBP parameters, including RT (r=0.283), AUC1 (r=0.659), AUC2 (r=0.674) were significantly positively correlated with the 24h average SBP, while the postoperative TTP (r=-0.413) and mTT (r =-0.472) were negatively correlated with 24h average SBP (P < 0.05). Multivariate Logistic regression analysis found that diabetes (OR=1.294), NT-proBNP (OR=1.395), number of antihypertensive agents (OR=2.135), pre-operation IMAX (OR=1.534), post-operation AUC2 (OR=2.417) and baseline dDBP (OR=2.038) were related factors for BP response (all P<0.05).